2019
DOI: 10.3390/su11226523
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Perceived Value, Intention to Use Hashtags, eWOM, and Brand Loyalty of Air Travelers

Abstract: This study analyzed the relationships between utilitarian value, hedonic value, intention to use an airline’s social networking service (SNS) hashtag, electronic word of mouth (eWOM), and brand loyalty. A research survey consisting of 220 samples was conducted with respondents who had experience using airline SNS hashtags. Finally, 204 answers were analyzed after excluding 16 unreliable answers. The results show that utilitarian value significantly influenced the intention to use hashtags, while hedonic value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 43 publications
1
19
0
3
Order By: Relevance
“…As self-disclosure in social media has boomed in recent years [31], many internet users share their life experience on social media, such as rating or posting a comment about a service or product, called e-WOM [32]. According to marketing research, positive e-WOM generates a positive attitude and recommendation for purchase, whereas negative e-WOM has the opposite effect [33]. Empirical human resources (HR) studies also found that employee experience leads to both positive and negative e-WOM [3], and positive (negative) e-WOM leads (or not) to recommendations of employers as employers of choice [8].…”
Section: Crowdsourced Employer Ratings and Employee Recommendations Omentioning
confidence: 99%
“…As self-disclosure in social media has boomed in recent years [31], many internet users share their life experience on social media, such as rating or posting a comment about a service or product, called e-WOM [32]. According to marketing research, positive e-WOM generates a positive attitude and recommendation for purchase, whereas negative e-WOM has the opposite effect [33]. Empirical human resources (HR) studies also found that employee experience leads to both positive and negative e-WOM [3], and positive (negative) e-WOM leads (or not) to recommendations of employers as employers of choice [8].…”
Section: Crowdsourced Employer Ratings and Employee Recommendations Omentioning
confidence: 99%
“…The data analysis method in the analysis used SEM (Structural Equation Modelling) techniques with the help of AMOS 24 application software. 2019) and Kim and Hyun (2019). Variable information sharing was measured through five indicators from Chinje and Chinomona (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hashtag atau tagar dapat dimaknai sebagai sistem kurasi percakapan publik melalui kata kunci yang digunakan di situs media sosial yang memudahkan untuk menemukan postingan atau informasi dengan tema atau isian konten tertentu (Kim & Hyun, 2019). Hashtag membantu mengkategorisasikan pesan komunikasi dalam konten media sehingga memungkinkan pengguna memahami komunikasi dalam topik tertentu (Figueiredo & Jorge, 2019).…”
Section: Kata Kunci: Nilai Utilitas; Kampanye Public Relations; Inten...unclassified
“…Hashtag membantu mengkategorisasikan pesan komunikasi dalam konten media sehingga memungkinkan pengguna memahami komunikasi dalam topik tertentu (Figueiredo & Jorge, 2019). Dalam penelitian ini penggunaan hashtag di media sosial merupakan tools atau alat berkomunikasi, dimana Kim dan Hyun (2019) menjelaskan bahwa audiens komunikasi memiliki persepsi nilai tertentu ketika menggunakan media berbasis teknologi infomasi ( Kim & Hyun, 2019).…”
Section: Kata Kunci: Nilai Utilitas; Kampanye Public Relations; Inten...unclassified